SMART GREEN INFRASTRUCTURE IN A SMART CITY – THE CASE STUDY OF ECOSYSTEM SERVICES EVALUATION IN KRAKOW BASED ON I-TREE ECO SOFTWARE - Siedlarczyk, Ewa; Winczek, Monika; Zięba-Kulawik, Karolina; Wężyk, Piotr (GeoScience Engineering, 2019)
It is a common perception that urban greenery does not bring any rational benefits, while profits from real estates are obvious. Therefore, the cities green infrastructure (urban forests, parks, trees, lawns, meadows, etc.) are constantly threatened with housing and development. However, urban greenery plays a substantial role in improving the quality of urbanites’ life, which is particularly significant in terms of predicted 70% urbanization rate by 2050. Healthy and well-managed city green infrastructure can improve air quality, remove particulate matters (PM) and CO2 sequestrate carbon, cool down the temperature or protect against winds. These functions of vegetation are known as ecosystem services (ES). Recognizing the value of ES provided by green infrastructure is crucial for urban planning and management in terms of assuring sustainable urban development. In our study, we used the i-Tree Eco (USDA Forest Service) software, which quantifies vegetation structure, environmental effects, and values of ES. The i-Tree Eco model is based on air pollution and local meteorological data along with the field data from the inventory of city vegetation. Requiring easy to collect (e.g. based on LiDAR 3D point clouds) input data and having a user-friendly interface, the i-Tree Eco has a potential of becoming a very useful tool for planners and managers in their everyday work. In this paper, we present a case study of ES evaluation for the “Krakowski Park” in Krakow (582 trees on 4.77 hectares, with the domination of Fraxinus excelsior, Ulmus laevis, and Betula pendula). For the analyzed 2015 year, the Krakowski Park trees stored in total 441.59 t of carbon, removed 184 kg of air pollutants and contributed to 220 m3 of avoided runoff. The total value of ecosystem services provided by Krakowski Park in the year 2015 was 5.096 EUR (8.76 EUR tree/year). In our further work, we intend to expand the ES evaluation on other green areas in Krakow and on a wider range of ES. Keywords: urban greenery, urban management and planning, air pollution, carbon sequestration, GIS http://doi.org/10.35180/gse-2019-0010